1998
DOI: 10.1093/molehr/4.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in human chorionic villi and decidua in normal and ectopic pregnancy

Abstract: To investigate possible effects of implantation on apoptosis, we examined the cleavage of DNA in human chorionic villi and decidua in intrauterine and ectopic pregnancy. Very limited but detectable cleavage of DNA was recognized in the chorionic villi and decidua in normal pregnancy. A ladder pattern, characteristic of the apoptotic breakdown of DNA, was present in the villi in tubal pregnancy. High molecular weight DNA was predominant in the decidua in tubal pregnancy. Quantitative analysis of low molecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…In the case of tubal EP, trophoblasts invade and erode the tubal muscular wall, and maternal blood vessels are opened (34). During this process, it is possible that the miRNAs are released into maternal circulation, as seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of tubal EP, trophoblasts invade and erode the tubal muscular wall, and maternal blood vessels are opened (34). During this process, it is possible that the miRNAs are released into maternal circulation, as seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, proliferation in intrauterine pregnancies, different from extrauterine pregnancies, may be downregulated by paracrine, possibly decidual (?) factors (Lala and Hamilton 1996;Kokawa et al 1998;Bischof et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with other studies that have demonstrated apoptosis in normal human placental tissue. In situ fragmented DNA characteristic of apoptosis [6,7,15], as well as oligosomal DNA laddering [16], have been reported in both first-and third-trimester placentae. In addition, light and electron microscopic techniques have been used to describe morphological features, including condensation of chromatin along the periphery of the nucleus and nuclear shrinkage, that are indicative of apoptosis in human placentae [7,17,18].…”
Section: Discussionmentioning
confidence: 99%